2020
DOI: 10.1039/d0ra04142d
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of the chelating agent 2,6-bis(1-(3-hydroxypropyl)-1,2,3-triazol-4-yl)pyridine: a combined XRD and DFT structural study

Abstract: Dispersion corrected DFT analysis in combination with single crystal X-ray structural analysis provides insights into the ability of PTD to chelate metal ions of radiotoxic waste from nuclear fuel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…16 The remarkable discrimination can originate from multiple effects, including supramolecular recognition from microscopic to macroscopic scales and the kinetic control at the interface. 16,53 Theoretical calculations confirmed that the extraction efficiency and selectivity are significantly affected by the capacity of EBBs solved in the IL phase assembling to [EBB] n clusters. 16 Herein, we believe that the idea of oxidation state control can further enhance the selectivity of the MSSA extraction method in the redox reactions involved in the MSSA process.…”
Section: +mentioning
confidence: 90%
“…16 The remarkable discrimination can originate from multiple effects, including supramolecular recognition from microscopic to macroscopic scales and the kinetic control at the interface. 16,53 Theoretical calculations confirmed that the extraction efficiency and selectivity are significantly affected by the capacity of EBBs solved in the IL phase assembling to [EBB] n clusters. 16 Herein, we believe that the idea of oxidation state control can further enhance the selectivity of the MSSA extraction method in the redox reactions involved in the MSSA process.…”
Section: +mentioning
confidence: 90%
“…These recent developments on the back-extraction An­(III) applied with hydrophilic N-type donor ligands inspired us to elucidate the electronic structures, bonding nature, and complexing ability of Am­(III)/Eu­(III) complexes with these ligands. Nowadays, density functional theory (DFT) calculations as a powerful tool have been used to evaluate the solvent extraction of f-block metal ions. There are several investigations on designing lipophilic ligands for the efficient separation of actinide ions. ,, However, there is a lack of theoretical studies on the selective separation of An­(III)/Ln­(III) with hydrophilic ligands. In this work, based on the structures of the experimentally available L a and L c ligands , and theoretically designed 2,9-bis­[(1-hydroylpropyl)-1 H -1,2,3-triazol-4-yl]-4,4-bipyridine ( L b , Scheme ), we explored the electronic structures of the three similar ligands with different bridging skeletons and examined their bonding nature and complexing ability with Am­(III)/Eu­(III) ions using scalar-relativistic DFT.…”
Section: Introductionmentioning
confidence: 99%